1955
DOI: 10.1063/1.1740695
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Crystallographic Study of Phase Transformation of Borax during Thermal Treatments

Abstract: Xray diffraction studies of microstructural transformations in singlecrystal silicon during current filamentation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1962
1962
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 3 publications
1
33
0
Order By: Relevance
“…The results reveal the borate response to the load through a two-stage transformation: rearrangement at low pressure and polymerization at high pressure. The pressure required to initiate the polymerization depends directly on the portion of fourfold-coordinated ( [4] B) boron in the sodium borates. We found that the polymerization occurs through three different mechanisms to form BO 4 tetrahedra with surface oxygen and nonbridging and bridging oxygen.…”
mentioning
confidence: 99%
“…The results reveal the borate response to the load through a two-stage transformation: rearrangement at low pressure and polymerization at high pressure. The pressure required to initiate the polymerization depends directly on the portion of fourfold-coordinated ( [4] B) boron in the sodium borates. We found that the polymerization occurs through three different mechanisms to form BO 4 tetrahedra with surface oxygen and nonbridging and bridging oxygen.…”
mentioning
confidence: 99%
“…In the range from room temperature to 480°C (where the sharp increase in the ionic mobility does not manifest itself), the thermal expansion along the crystallographic axes is nearly isotropic (Table 1, 2). However, at temperatures higher than 480°C, the significant changes in the unit cell angles lead to anisotropic thermal deformations of the α-Na 2 B 4 O 7 structure ( Table 2).…”
Section: Thermal Deformations Of the α-Na 2 B 4 O 7 And β-Nab 3 O 5 Bmentioning
confidence: 92%
“…This effect was also observed using differential thermal analysis: the effect at a temperature of 773°C in [7] was interpreted as congruent melting of the α triborate, although X-ray diffraction data were also absent. The effect at a temperature of 675°C was revealed in [2,3].…”
Section: Peritectic Melting Of the β-Nab 3 O 5 Boratementioning
confidence: 99%
See 2 more Smart Citations